CASE REPORT: PARANOID SCHIZOPHRENIA - Siti Elita Syabaniyah; Ryan Aditya (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Schizophrenia is a mental disorder characterized by distortion of reality, disorganization, and psychomotor poverty. Schizophrenia is characterized by positive symptoms such as hallucinations, delusions, bizarre behavior and thought disorders and negative symptoms such as flat or blunted affect, alogia, anhedonia and deficits in social interaction. Schizophrenia disorders persist for at least six months and there must be at least one month of symptoms. Schizophrenia affects approximately 1% of the world's population. Although schizophrenia treatment can improve symptoms, it cannot restore normal function in most patients. Treatments that can be given to schizophrenia sufferers such as oral antipsychotics, especially second-generation such as risperidone, olanzapine, aripiprazole are recommended for initial treatment of acute psychosis. Case illustration is a 27-year-old male patient with complaints of hearing voices that cannot be heard by others and making it difficult for the patient to sleep. Management of this patient was given quetiapine 2x400 mg and lorazepam 1x1 mg. The result of this patient's management is an improvement in clinical symptoms. The conclusion of this case report is that paranoid schizophrenia is a case that is easy to relapse and can even become chronic, so it is necessary to do the importance of medication compliance, appropriate social support in order to improve social function in patients.